(untitled) (Materiali di Estetica. Terza serie, 2017)
The article tries to approach the problem of Kafka’s Judaism by reading the Philosophical Fragment (March 1906) as a short, ironical midrash haggadah, that the young writer would have fast unconsciously composed while he was glossing some of Brod’s aesthetic papers. The comment itself, that is also a disproof of Brod’s thesis, is formulated as a “midrash-haggadah”. Translating in a profane shape the attitude of kavanah as mystic intention, this short, humble deconstruction wheels obsessive around the only theme of Tiredness (die Ermüdung). Keywords: Judaism; Midrash; Irony; Tiredness